(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
There is a need to use certain cutting-edge 1D and 2D NMR methods due to the growingcomplexity of natural chemicals and their synthesized related counterparts. The primary goals of thiswork are to (1) explain the most important 1 H, 13C, and 15N NMR properties of three- to six-memberedheterocyclic compounds, and (2) explore the use of many 1D and, more importantly, 2D NMR methods inthe structural elucidation of these compounds. Element studies, UV, IR, 1H, and 13C NMR, and ESI-MSspectrum data were used to determine the structures of the compounds. Antiamoebic activity againstEntamoeba histolytica was measured in vitro and compared to that of the standard antiamoebicmedication, metronidazole. The IC50 values for E. histolytica were found to be lower for 10 of the 30compounds tested for antiamoebic action (compounds 5, 6, 15, 18, 25–30). Preliminary findingssuggested that the antiamoebic action was improved when the phenyl ring at position 3 of the pyrazolinering was replaced with either 3-chloro or 3-bromo.